Uji Aktivitas Antioksidan Ekstrak Biji Kepuh (Sterculia foetida) serta Potensinya dalam Uji Neutrofil untuk Imunitas Mencit (Mus musculus) - Ngginak, James; Sabuna, Alan Ch.; Bullu, Novi Ivone; Koy, Vedy Yeriel (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The purpose of this study is to test the Â antioxidant activity of kepuh seed extract (Sterculia foetida) as well as its potential in neutrophil testing for mouse immunity (Mus musculus). This study was experimental by looking at the number or ratio of neutrophils in mice that had been given stress treatment in the form of wounds on the body of mice after being given kepuh seed extract. The antioxidant activity test is carried out using the DPPH method, while the neutrophil test can be carried out using the flow cytometry method. The results of the antioxidant activity test using the DPPH method (IC 50) showed a result of 18.0361 mg/mL. The regression results of levels (mg/mL) vs antioxidant activity (%) showed that the higher the level of kepuh seed extract, the higher the percentage of antioxidant ability available. Based on the results of the research, it can be concluded that; (1) The concentration of 18.0361 mg/mL in chickpeas (Sterculia foetida) can inhibit free radicals in the body, so it can be said that chickpeas (Sterculia foetida) have strong antioxidant activity; (2) The higher the content of kepuh seed extract, the higher the percentage of antioxidant ability.